Etno-racial self-identification patterns of indigenous population in household surveys in Peru - Moreno, Martín (2014)
This study defines and characterizes etno-racial self-identification patterns of the Peruvianpopulation employing the Encuesta Nacional de Hogares (Enaho) 2012. For this purpose, we have employed a module with questions recently added to this survey, in order to approach empirically to the notion of identity, combining the dimensions of native language, self-acknowledgment and the notion of indigenous population. The results are based on a latent classes analysis employing, at the same time, the information in this questions in order to identify four possible etnoracial identities. These identities are intertwined in the self-acknowledgment process with certain ancestors and customs, and also the one based on language. With the methodology and  the  data  collected,  we  haven’t  found  evidence that point that ethnic identities are multiple and fluent. The ethnic identities show certain heterogeneity in terms of the dimensions they are composed.